Application of Biochar Compost Residue and Liquid Organic Fertilizer from Tofu Waste on Pakcoy Plants' Growth and Yield - Margareta Siba Soge; Natalia Desy Djata Ndua; Deseriana Bria (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
This research was conducted from October to November 2024 in the greenhouse and laboratory of the Faculty of Agriculture, Science, and Health at Timor University. The purpose of this study was to determine the effect of the interaction between biochar compost residue and tofu waste POC on the growth and yield of pak choy plants. The study employed a completely randomized design (CRD) factorial experiment consisting of two factors. The first factor was biochar compost residue, and the second factor was tofu waste POC residue. The biochar compost factor consisted of three levels: 0% biochar compost, 10% biochar compost (0.4 kg biochar compost mixed with 3.6 kg soil), and 30% biochar compost (1.2 kg biochar compost mixed with 2.8 kg soil). The tofu waste POC factor also had three levels: 0 mL/L water, 100 mL/L water, and 200 mL/L water. These factors resulted in nine treatment combinations, each replicated three times, for a total of 27 experimental units. The results showed no significant interaction between biochar compost residue and tofu waste POC. However, the biochar compost residue alone had a substantial effect on plant growth parameters. This research provides valuable information for agriculture by helping to determine the use of biochar compost as a fertilizer and growing medium in pak choy cultivation, enhancing growth and yield.